TUBERCULOSIS EDUCATION: INTRODUCTION, EFFECTIVE TREATMENT, AND SIDE EFFECTS AS AN EFFORT TO MAINTAIN INDIVIDUAL AND ORPHANAGE ENVIRONMENT HEALTH - Ratna Sofaria Munir; Handayani; Renny Novi Puspitasari; Bella Az Zahra; Fatimatuz Zahro; Anfasa Luthfi Arasya; Putri Najwa Tazkia; Retno Diah Putri Ekayanti (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Indonesia still ranks second as the country with the most tuberculosis (TB) cases in the world. The increasing number of pulmonary TB patients in Indonesia is caused by unhealthy behaviors, such as families still using the same eating or drinking utensils, lack of lighting in the house, or patients spitting carelessly. One strategy is to find all TB cases and treat them until cured, to stop TB transmission. TB control efforts require the involvement of all sectors, including non-health. The behavior of caregivers in orphanages plays a very important role in reducing the risk of pulmonary TB transmission in children. On the other hand, orphanage residents, consisting of children and adolescents, often lack sufficient access or information about TB prevention and treatment. Based on this, this community service activity was conducted in the form of socialization about tuberculosis, including introduction, effective treatment, and side effects. The method used was counseling on TB disease, effective tuberculosis treatment, and how to avoid drug side effects. The number of participants was 16 people. The results showed a good increase in knowledge of 81.25%. Participants were very enthusiastic during the question and answer discussion session. Conclusion: The counseling activity successfully increased participants' knowledge and showed high enthusiasm, indicating that targeted education is very important in raising awareness about TB prevention and treatment.